Islam and Politics in Central Asia: By Mehrdad Haghayeghi. New York: St. Martin's Press. 1995. (American Journal of Islam and Society, 1997)
The emergence of the five independent and predominantly Muslim statesKazakhstan,Kyrgyzstan, Tajikistan. Turkmenistan, and Uzbekistan-in theaftermath of the collapse of the Soviet Union raises the issue of the role of Islamin their future development. Since Islam does not allow a separation of religionand politics, Islamic political panies have already been active, albeit with differentintensity, in these countries. None of these countries has had a history ofindependence; for a long time, they were colonized (their most recent history ofcolonization goes back to the 1860s. when the Russians began to conquer andcolonize the Central Asian villages) by czarist Russia, then from 1917 by thecommunist czars. Consequently, after independence their political elite (for themost part, former communists) remain substantially unfamiliar with the practiceof democratic governance. As such, even after changing the names of communistparties in their respective countries, they essentially practice authoritarianpolicies in which little or no political pluralism is tolerated. Therefore. anyevolution of democracy in these statei in the immediate or middle-range futureis unlikely. However. Kazakhstan and Kyrgyzstan are two exceptions to thisrule.Not coincidentally. both Kazakhstan and Kyrgyzstan top the list of ethnicallypluralist states, and their economies are doing well compared to their CentralAsian counterparts. However, this ethnic pluralism has not only polarized theirpopulations along indigenous and Russian lines but also keeps their leaders fromallowing any substantial role for lslamist parties. Uzbekistan. Turkmenistan,and Tajikistan have a lesser problem emanating from ethnic pluralism.However, the lion's share of these countries' problems stems from the acutelyauthoritarian nature of their leader hip, and, more imponant, their severe economicunderdevelopment. One has to keep these variables in mind as one readsMehrdad Haghayeghi's book, Islam and Politics in Central Asia.Describing the presence of Islam in Central Asia, The author states that "thesedentary populations of the oasis enclaves and the tribal populations of theSteppe and the surrounding regions" were differently influenced by Islam. Hegoes on to observe:The enormous size and remoteness oft.he Steppe, the lack of adequate military manpower.the political instability at the heart of the Arab empire, and the absence of ...